2013
DOI: 10.5539/ibr.v6n9p93
|View full text |Cite
|
Sign up to set email alerts
|

Online Promotional Games: Impact of Flow Experience on Word-of-Mouth and Personal Information Sharing

Abstract: Viral campaigns widely use online promotional games. They are an innovative and a compelling way to capture the attention of the target audience, and encourage consumers to interact with brands. The goal is to offer consumers a content that influence customer behaviour. As more immersive games are developed, online promotional games possess a number of features that make them a compelling opportunity for the study of flow. Flow is a mental state of operation in which a person is fully immersed in what he or sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
2
13
0
1
Order By: Relevance
“…If a mismatch between challenge and skill occurs, the state of flow can be inhibited. As demonstrated by Jin (2011Jin ( , 2012 and Renard (2013), the combination of a high level of challenge and a high level of skill resulted in the highest level of flow state. Interestingly, however, Wang and Chen (2010) found that challenging games induced more flow experiences than those that attempted to match game challenge to skills, although the latter demonstrated greater project performance.…”
Section: User-game Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…If a mismatch between challenge and skill occurs, the state of flow can be inhibited. As demonstrated by Jin (2011Jin ( , 2012 and Renard (2013), the combination of a high level of challenge and a high level of skill resulted in the highest level of flow state. Interestingly, however, Wang and Chen (2010) found that challenging games induced more flow experiences than those that attempted to match game challenge to skills, although the latter demonstrated greater project performance.…”
Section: User-game Characteristicsmentioning
confidence: 99%
“…Although it is generally the case that highest flow is attained when game challenge and player skill are well balanced or matched (Jin, 2011(Jin, , 2012Renard, 2013), Schneider and Cornwell (2005) found that novice players experienced more flow than experienced players in low-challenge tasks. They concluded that the challenge presented by the game was not high enough for experienced players.…”
Section: User-game Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the online environment, the experience is often comprised by the inaccessibility of service staff along with machine responses (Yang;Jun, 2002). Over recent years however, technological advancements through web 2.0 functionality and social media have enabled the development of a more interactive social environment that provides B2B, B2C and C2C communication (Renard, 2013). The introduction of online social functions has developed what we see as the 'social customer' raising the expectation on being able to communicate online (Greenberg, 2010).…”
Section: Customer Supportmentioning
confidence: 99%